Deep brain stimulation for dystonia treatment in cerebral palsy: efficacy exploration - Haoyang Zheng; Duo Zhang; Wei Xiang; Yong Gan; Zesheng Peng; Yuyi Wu; Peng Fu (Experimental Biology and Medicine)
Dystonia, a challenging movement disorder, poses significant therapeutic challenges due to its resistance to treatment, resulting in both physical impairment and substantial mental distress, ultimately impacting overall quality of life. Cerebral palsy (CP) is a major non-genetic cause of secondary dystonia, characterized by diverse clinical presentations. This study aims to comprehensively evaluate the effectiveness of deep brain stimulation (DBS) as a therapeutic intervention for individuals with dystonic CP. We conducted a systematic analysis of studies assessing the safety and effectiveness of DBS, with a focus on its long-term outcomes [PROSPERO (Unique identifier: CRD42023399285)]. We examined factors that influence treatment response and proposed strategies to enhance patient quality of life. DBS, especially when targeting the basal ganglia or innovative targets, shows promise as a therapeutic approach for dystonic CP. While existing controlled studies confirm its safety and effectiveness, a thorough evaluation of long-term efficacy remains crucial. This research highlights the potential of DBS in improving the lives of individuals with dystonic CP, providing hope for further refinement, innovation, and broader clinical application of this therapeutic approach.